Food quality profile of pounded yam and implications for yam breeding - Otegbayo, B.; Oluyinka, O.; Tanimola, A.; Fawehinmi, B.; Alamu, A.; Bolaji, T.; Madu, Tessy; Okoye, B.; Chijioke, Alamu Ugo; Ofoeze, M.; Alamu, E.O.; Adesokan, M.; et al. (Wiley, 2024)
BACKGROUND Assessment of the key preferred quality traits in pounded yam, a popularly consumed yam food product in West Africa, is often done through sensory evaluation. Such assessment is time-consuming and results may be biased. Therefore, there is a need to develop objective, high-throughput methods to predict the quality of consumer-preferred traits in pounded yam. This study focused on how key quality traits in pounded yam proposed to yam breeders were determined, measured by biophysical and biochemical methods, in order to shorten the breeding selection cycle through adoption of these methods by breeders.